2009
DOI: 10.1097/prs.0b013e31819b69b1
|View full text |Cite
|
Sign up to set email alerts
|

Outfracture of the Inferior Turbinate: A Computed Tomography Study

Abstract: BACKGROUND: Various surgical treatment modalities are available for inferior turbinate (IT) hypertrophy. Each is related with well-established complications, but still there is a lack of consensus on the optimal technique. Outfracture of the IT is thought to be a minimal destructive procedure among all other reductive turbinate interventions. Our aim was to assess the long term effects of IT outfracture technique in patients with mild or moderate IT hypertrophies. METHODS: Twenty ITs in 10 patients were outfra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…1,28 Because of reports of these complications, a less radical approach to the problem evolved, and partial turbinate reduction procedures were adopted. 8,11 In 1924, the submucous resection was described; it was further popularized in the 1950s. 1,12,29 During the subsequent several decades, submucous reduction and surgical turbinate reduction were widely practiced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,28 Because of reports of these complications, a less radical approach to the problem evolved, and partial turbinate reduction procedures were adopted. 8,11 In 1924, the submucous resection was described; it was further popularized in the 1950s. 1,12,29 During the subsequent several decades, submucous reduction and surgical turbinate reduction were widely practiced.…”
Section: Discussionmentioning
confidence: 99%
“…1,12,29 During the subsequent several decades, submucous reduction and surgical turbinate reduction were widely practiced. 8 Beginning in the 1990s, however, there was a greater emphasis on research and development of new technologies for turbinate reduction, such as cryosurgery, 26 electrocautery, 11 radiofrequency ablation, 15Y19 laser cautery, 20Y25 and microdebridement of the turbinate mucosal tissues. 30 This study demonstrates that most of the ASPS members polled include an evaluation of inferior turbinate hypertrophy as part of a comprehensive rhinoplasty consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unpredictability of the effects of inferior turbinate outfracture has also been noted by Buyuklu et al 3 They measured the distance from the lateral border of the inferior turbinate bone to the lateral wall of the nose, in Turkish patients with mild to moderate enlargement of the inferior turbinates who were undergoing septoplasty and inferior turbinate outfracture. The same outfracture technique was used.…”
Section: Discussionmentioning
confidence: 92%
“…Mucosal-sparing techniques are currently in favor due to lack of associated crusting, synechiae, bleeding, and discomfort. Inferior turbinate outfracture is the simplest method, and CT examination postoperatively showed that lateralization had been maintained at 9-month follow-up [20]. Submucous resection by traditional techniques or in the microdebrider-assisted technique appears to create the greatest volumetric reduction with the longest-lasting result [21].…”
Section: Turbinate Managementmentioning
confidence: 98%